Crossover from the Mott Variable Range Hopping Conduction Regimeto Nearest Neighbor Site Hopping Regime in ZnSxSe1-x Thin Films - Mounir, E.; Mabchour, H.; Ennajh, D.; El oujdi, A.; El kaaouachi, A.; Ait Hammou, B.; Echchelh, A.; Dlimi, S.
In this work, we study the behavior of resistivity as a function of temperature and for several samples of ZnSxSe1-x thin films with x = 0, 0.2, 0.4, 0.5, 0.6, 0.8 and 1.0 respectively. In fact, we re-analyze in our investigation experimental measurements obtained by M. Popa et al. [1] in the range of temperature from 300 K to 500 K. We showed that the resistivity follows a nearest neighbor site hopping conduction mechanism with = () for very high temperatures and Mott variable range hopping conduction with = ()/ for relatively low temperatures. The crossover between the two regimes can be explained by the competition between the localization length scale and the hopping length scale .
Keywords: Physics